SYNGAP1-DEE: A visual sensitive epilepsy. Issue 4 (April 2021) - Lo Barco, Tommaso; Kaminska, Anna; Solazzi, Roberta; Cancés, Claude; Barcia, Giulia; Chemaly, Nicole; Fontana, Elena; Desguerre, Isabelle; Canafoglia, Laura; Hachon Le Camus, Caroline; Losito, Emma; Villard, Laurent; et al.
Highlights: We analyzed 72 EEGs from 15 unreported individuals exhibiting developmental encephalopathy with pathogenic SYNGAP1 variants. 72% of awake seizures occurred at eye-closure or with eyes closed. Fixation-off and eye closure were the main triggers for seizures in this SYNGAP1 cohort. Abstract: Objective: To further delineate the electroclinical features of individuals with SYNGAP1 pathogenic variants. Methods: Participants with pathogenic SYNGAP1 variants and available video-electroencephalogram (EEG) recordings were recruited within five European epilepsy reference centers. We obtained molecular and clinical data, analyzed EEG recordings and archived video-EEGs of seizures and detailed characteristics of interictal and ictal EEG patterns for every patient. Results: We recruited 15 previously unreported patients and analyzed 72 EEGs. Two distinct EEG patterns emerged, both triggered by eye closure. Pattern 1 (14/15 individuals) consisted of rhythmic posterior/diffuse delta waves appearing with eye-closure and persisting until eye opening (strongly suggestive of fixation-off sensitivity). Pattern 2 (9/15 individuals) consisted of diffuse polyspike-and-wave discharges triggered by eye closure (eye-closure sensitivity). Both patterns presented in 8/15. Including archived video-EEG clips of seizures from 9/15 patients, we analyzed 254 seizures. Of 224 seizures experienced while awake, 161 (72%) occurred at or following eye closure. In 119/161, pattern 1 preceded an atypical absence, myoclonic seizure or myoclonic absence; in 42/161, pattern 2 was associated with eyelid myoclonia, absences and myoclonic or atonic seizures. Conclusions: Fixation-off and eye closure were the main triggers for seizures in this SYNGAP1 cohort. Significance: Combining these clinical and electroencephalographic features could help guide genetic diagnosis.